Design and modeling of solar water pumping system in Diyala region - Mohammed Hasan Ali; Raghad Ali Mejeed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In recent years, solar panels have become increasingly popular for converting solar energy is converted into electrical energy. The solar panel can be utilized as part of a larger solar system that is connected to the power grid or as a stand-alone system. Every day, the world receives 84 Terawatts of energy, yet we only use about 12 Terawatts. For optimal energy conversion, the tracking mechanism will keep the solar panel perpendicular to the sun at all times. In this setup, photo resistors will be employed as sensors. A light detection system, a microprocessor, a gear motor system, and a solar panel will make up the system. When compared to solar panels without tracking equipment, our system will produce up to 40% more electricity. Improvements to the board's efficiency include the addition of a dust sensor. The dust on the board is also detected by the sensor, which activates a pump inside the tank. It uses the Arduino to pump water onto the board to clean it of dust and maintain its efficiency. There is also a water sensor. When the tank's water level falls below a certain level, the attached pump activates.